PENGEMBANGAN SISTEM INFORMASI PELAYANAN MEDIS RAWAT JALAN DENGAN PENDEKATAN SYSTEM DEVELOPMENT LIFE CYCLE MODEL WATERFALL: STUDI KASUS RUMAH SAKIT DAAN MOGOT TANGERANG - Entin Sutinah; Moch.Arif Wicaksono; Riza Syahrial (LPPM STMIK ANTAR BANGSA, 2014)
Abstract__ Data can be presented quickly is the dream of every decision. Daan Mogot Hospital is a health service that currently does not have a computerization system, causing the length of patient data search, no patient data updates so that the difficulty in knowing the number of outpatient medical services and transaction systems are slow. From interviews and direct study of spaciousness, it appears that Dan Mogot Hospital is in need of a computerized system. In applying this computerized system using Microsoft Visual Basic sofeware and in making their reports using the report the data, while the server, we choose the server core 2 dou., And to print the required reports using the inkjet printer, this research with SDLC approach with a model waterfall. As a result of this research, it turns out by using a computerized system, one can get data very quickly. Course of profits is also a disadvantage that the parties who are not incapabilty can get data from computers that have been netted. Therefore computer security should come first in creating a computerized system.